Description of polarisation dependence of two-photon absorption in silicon avalanche photodiodes - Donegan, John; Bradley, Louise (My University, 2010)
A simple formula is obtained that very accurately describes the level of two-photon absorption (TPA) generated by elliptically polarised light in silicon avalanche photodiodes (Si-APDs). The dichroism parameter necessary to describe the polarisation dependence of TPA in Si-APDs at room temperature is determined to be +0.372 in the region of 1550 nm.
PUBLISHED
Keywords: Physics; Photocurrent; Nanoscience & Materials